Optimaslisasi Penghimpunan dan Penguatan Literasi Wakaf Tunai Melalui Peranan Penyuluh Agama - Agus Suaidi Hasan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Waqf is an Islamic social financial instrument with significant potential for development. Cash waqf is a powerful tool that bridges social gaps. By leveraging the potential of waqf, economic development can proceed smoothly. Indonesia, as the largest Muslim country and one of the most generous in the world, fully understands this. It is inevitable that waqf becomes a potential that must be maximized. However, in reality, this potential still falls short of expectations. This is based on various factors that motivate waqf, including religiosity, comfort, and literacy. Therefore, innovation is needed to optimally collect waqf funds. This study used a qualitative approach with a literature study method, with data obtained from interviews, electronic media, books, and journals. The results of the study include the development of a collection model through the role of religious instructors as the spearhead of agencies collecting waqf funds and providing understanding or literacy about cash waqf.